Robotic Guidance for S2-Alar-Iliac Screws in Spinal Deformity Correction. Issue 1 (February 2017) - Bederman, S. Samuel; Hahn, Peter; Colin, Vincent; Kiester, P. Douglas; Bhatia, Nitin N.
Abstract : Study Design: A retrospective cohort study of patients who underwent S2-alar-iliac (S2AI) screw insertion using robotic guidance in long constructs for spinal deformity correction extending to the sacrum performed at a single institution. Objective: To assess and evaluate the feasibility and accuracy of robotic guidance for S2AI screw insertion. Summary of Background Data: Pelvic fixation has become a common adjunct to long fusions extending to the sacrum. The S2AI method possesses advantages over the traditional Galveston technique. S2AI involves finding a pathway from S2 across the sacral ala and the sacroiliac joint into the ilium. Robotic guidance is a new modality for implant insertion that has shown high accuracy. Methods: We identified all patients who underwent robotic-guided S2AI screw insertion in long constructs extending to the sacrum. Cortical breaches and protrusions, assessed on postoperative imaging, and complications were recorded. Results: Fourteen patients (31 screws) underwent S2AI screw insertion using robotic guidance and free-hand probing. Average screw length was 80 mm (range, 65–90 mm). All trajectories were confirmed as accurate (no proximal breaches). Screw insertion, performed manually, resulted in 10 protrusions <2 mm, 1 by 2–4 mm, and 6 by ≥4 mm. No screw was intrapelvic or risked any visceral or neurovascular structures and none required removal or revision. Longer screws (>80 mm) were associated with distal protrusion. Conclusions: Robotic-guided S2AI screws are accurate and a feasible option. Although no complications from protrusion were identified, larger studies and instrumentation modifications are required to assess the clinical acceptance of robotic guidance in sacropelvic fixation.